Antipredatory reaction of the leopard gecko Eublepharis macularius to snake predators - Landová, Eva; Musilová, Veronika; Polák, Jakub; Sedláčková, Kristýna; Frynta, Daniel (Current zoology, 2016)
Ability to recognize a risk of predation and react with adaptive antipredatory behavior can enhance fitness, but has some costs as well. Animals can either specifically react on the most dangerous predators (threat-sensitive avoidance) or they have safe but costly general wariness avoiding all potential predators. The level of threat may depend on the predator's foraging ecology and distribution with the prey with sympatric and specialist species being the most dangerous. We used 2 choice trials to investigate antipredatory behavior of captive born and wild-caught leopard geckos confronted with different snake predators from 2 families (Colubridae, Boidae) varying in foraging ecology and sympatric/allopatric distribution with the geckos. Predator-naïve subadult individuals have general wariness, explore both chemically and visually, and perform antipredatory postures toward a majority of snake predators regardless of their sympatry/allopatry or food specialization. The most exaggerated antipredatory postures in both subadult and adult geckos were toward 2 sympatric snake species, the spotted whip snake Hemorrhois ravergieri, an active forager, and the red sand boa Eryx johnii, a subterranean snake with a sit-and-wait strategy. In contrast, also subterranean but allopatric the Kenyan sand boa Eryx colubrinus did not elicit any antipredatory reaction. We conclude that the leopard gecko possesses an innate general antipredatory reaction to different species of snake predators, while a specific reaction to 2 particular sympatric species can be observed. Moreover, adult wild caught geckos show lower reactivity compared with the captive born ones, presumably due to an experience of a real predation event that can hardly be simulated under laboratory conditions.
Keywords: antipredation; sympatric; lizard; posture; 2 choice trial.; allopatric